The Effectiveness of Counseling Leaflet Method Against Changes in Pregnant Women's Knowledge of the Third Trimester of Post-Saline Contraceptives - Asmirati; Mitra Asriani Amin; Nabila; Aldina Lestari; Sri Eka Juniarli; Murida Wiryanti (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
Family planning is an example of direct policy in population control. Strategic intervention in safe motherhood efforts is stated as 4 pillars, namely family planning, antenatal care, clean and safe childbirth, and essential obstetric services. This study used a quasi-experimental research design with pre-test and post-test group designs. Using 50 respondents as a selected sample using Purposive Sampling. The results of the statistical signed rank test obtained the average knowledge of respondents before being given an intervention with a leaflet of 9.76 while after being given an intervention of 16.34 with a P value (Asymp. Sig. (2-tailed)) 0.000 where <0.05 so that it can be concluded that there is a meaningful difference before and after the respondent is given the intervention with leaflet. This proves that leaflet media has a great influence on increasing knowledge.